2020
DOI: 10.1007/s11739-020-02512-y
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound as diagnostic tool for SARS-CoV-2 infection

Abstract: The aim of this study was to explore the role of lung ultrasound (LUS) in the diagnosis of SARS-CoV-2 infection and to verify its utility in the prediction of lung disease's severity and outcome. Fifty-three consecutive patients presenting to the Emergency Department of Santa Maria delle Grazie Hospital with high suspicion of SARS-CoV-2 infection underwent diagnostic test for SARS-CoV-2 on samples obtained from nasopharyngeal swab as well as complete proper diagnostic work-up that included clinical evaluation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 17 publications
2
50
0
5
Order By: Relevance
“…Previous studies in COVID-19 showed that LUS semi-quantitative evaluation provided useful diagnostic [ 14 ] and prognostic [ 15 , 16 ] information, while it correlated well with worsening respiratory insufficiency [ 14 ]. In our sample, we reported similar results; however, in comparison to others [ 14 , 15 ], we observed lower values of LUS scores and higher PaO2/FiO2, possibly partly explained by the non-critical care setting of our population [ 9 ]. Of note, COVID-19 is featured by quite heterogeneous clinical behavior, ranging from asymptomatic cases to different degrees of flu-like symptomatology and bilateral pneumonia complicated by respiratory failure [ 5 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in COVID-19 showed that LUS semi-quantitative evaluation provided useful diagnostic [ 14 ] and prognostic [ 15 , 16 ] information, while it correlated well with worsening respiratory insufficiency [ 14 ]. In our sample, we reported similar results; however, in comparison to others [ 14 , 15 ], we observed lower values of LUS scores and higher PaO2/FiO2, possibly partly explained by the non-critical care setting of our population [ 9 ]. Of note, COVID-19 is featured by quite heterogeneous clinical behavior, ranging from asymptomatic cases to different degrees of flu-like symptomatology and bilateral pneumonia complicated by respiratory failure [ 5 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic ultrasound (US) was used to assess the presence of residual lung abnormalities. The sonographic examination was performed according to the protocol described by Bosso et al A convex or linear array probes were used to explore 12 wall zones, 6 per side, with the patient in a sitting position [ 13 ]. Each zone was scored according to the lung US pattern (score 0: presence of A-lines or fewer than 3 isolated B-lines, score 1: presence of multiple well-spaced B-lines, score 2: presence of coalescent B-lines, score 3: presence of lung consolidation).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies are advocating radiologic imaging such as chest radiograph (CXR), chest ultrasound (US), lung ultrasound (LUS), and particularly chest computed tomography (chest CT) as complementary and, in some cases, as standard diagnosis method of COVID-19. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] Patients who developed COVID-19 pneumonia shared similar lung abnormalities. 48 Peripheral ground-glass opacities, multiple bilateral consolidation, crazy paving patterns, and reticular pattern are standard features found in chest CT of pneumonia patients.…”
Section: Radiology-based Detectionmentioning
confidence: 99%